Atypical Manometric Abnormality of the Lower Esophageal Sphincter: A Procedure-Related, Stress-Induced Phenomenon? - Bhuvanendram Indrakrishnan; William G Paterson (Canadian Journal of Gastroenterology)
Stress-induced esophageal contraction abnormalities have been well documented in the literature, but relatively little is known about stress-related lower esophageal sphincter (LES) dysfunction. Two patients are described in whom initial manometry studies revealed LES hypertension and impaired LES relaxation. Both patients were markedly anxious and agitated during the initial study. However, when the manometry was repeated with the patients in a calmer state, LES pressure and function were normal. These cases demonstrate the need to be aware of stress-related LES dysfunction. If this phenomenon is not identified in the appropriate settings, it could lead to significant errors in management.